2008
DOI: 10.1302/0301-620x.90b10.20378
|View full text |Cite
|
Sign up to set email alerts
|

The Metasul metal-on-metal articulation in primary total hip replacement

Abstract: We report the clinical and radiological outcome at ten years of 104 primary total hip replacements (100 patients) using the Metasul metal-on-metal bearing. Of these, 52 had a cemented Stuehmer-Weber polyethylene acetabular component with a Metasul bearing and 52 had an uncemented Allofit acetabular component with a Metasul liner. A total of 15 patients (16 hips) died before their follow-up at ten years and three were lost to follow-up. The study group therefore comprised 82 patients (85 hips). The mean Oxford … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 22 publications
6
45
0
1
Order By: Relevance
“…Our results and those of other published studies demonstrate that ARMD does occur with small-diameter heads in MoM THA [5,8,12,19,20,39,44,48]. Unlike large-diameter MoM THA, in which aseptic loosening and early failure of ingrowth appear to be the main failure modes with ARMD appearing in the early to midterm, MoM THA with a titanium shell and cobalt-chromium insert had very low rates of aseptic loosening.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Our results and those of other published studies demonstrate that ARMD does occur with small-diameter heads in MoM THA [5,8,12,19,20,39,44,48]. Unlike large-diameter MoM THA, in which aseptic loosening and early failure of ingrowth appear to be the main failure modes with ARMD appearing in the early to midterm, MoM THA with a titanium shell and cobalt-chromium insert had very low rates of aseptic loosening.…”
Section: Discussionsupporting
confidence: 63%
“…For the seven other devices included, small-and large-diameter bearings were grouped together by brand, including the M2a-Taper with 28-and 32-mm heads and Magnum (38-54 mm [39]. In other studies of the Metasul bearing, reported frequencies of ARMD were 2.6% (three of 125) at 3 to 9 years followup [8], 3% (one of 33) at mean followup of 5 years (range, 3-5 years) [5], and 2.4% (two of 85) at a mean followup of 11 years (10-12 years) [12]. In a report by Hwang et al of 141 patients (180 hips) with Metasul bearings reviewed at mean followup of 14 years (range, 12-18 years), nine hips had symptomatic groin pain with pseudotumor diagnosed in two (1.1% [two of 180]) [20].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Clinical studies have shown that a 98.6-99% survival rate could be expected ten years after a contemporary MOM hip replacement with a near absence of osteolysis [4,5]. Also, a low amount of wear on retrieved implants and in vivo has been reported [20,21,23], confirming preliminary hip simulator tests [24] and former clinical data [15,22].…”
Section: Introductionsupporting
confidence: 54%
“…In support, a recent study noted impingement occurred in 83% of 28-mm and 32-mm CoC retrievals [20]. Such evidence may indicate why some 28-mm MoM series showed good results over 7 to 15 years [13,78] and others showed lesser success [4,21,41]. Because our 28-mm MoM retrievals were referred into La Pitie Hospital, the incidence of neck notching in the general population could not be determined.…”
Section: Discussionmentioning
confidence: 82%